SINERGISITAS ANTARA PEMERINTAH PUSAT DAN PEMERINTAH DAERAH SERTA SWASTA DAN MASYARAKAT DALAM PEMBANGUNAN RUMAH SUSUN SEDERHANA SEWA (RUSUNAWA) DI KOTA PEKANBARU (Studi Kasus Di Kecamatan Tenayan Raya) - syafriyanto "; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is motivated by Act No. 25 of 2004 on the National Development Planning system. Then followed the Law No. 20 of 2011 on the Flats. The problems in the implementation of development Rusunawa Pekanbaru city because the city has the problem of slums and urban spatial planning issues, so that the city government is based on real conditions in the field to submit a proposal to the central government in order Rusunawa development. The process of construction of rental flats are finished but until now have not been able to the public housing buildings inhabited, it is in because the central government had not occupy the contents of the draft agreement in the public housing development agreement, which explained that if the delivery of public housing construction is completed, the building is handed over kepemerintah center in conjunction with a budget that has been agreed, but after the construction is completed rusunawa occupy the central government can not draft the agreement so that the private sector can not be handed over to the central government.Based on the analysis and observation in the field can be concluded that the synergy of the central government, local government, private sector and communities to the development of a simple flat rental (public housing) in the city of Pekanbaru (case study in the district Tenayan highway) is not maximized carried. While the factors that inhibit synergy central government, local government, private sector and communities to the development of a simple flat rental (public housing) in the city of Pekanbaru (case study in the district Tenayan highway) is a system of central government funding, weak local government resources humans, whereas the private sector constraints in terms of building public housing handover with the central government.Keywords: Synergy, Development, Rusunawa